A web-based GIS platform for the safe management and risk assessment of complex structural and infrastructural systems exposed to wind. (March 2018) - Repetto, Maria Pia; Burlando, Massimiliano; Solari, Giovanni; De Gaetano, Patrizia; Pizzo, Marina; Tizzi, Marco
Abstract: This paper describes an extensive research activity, carried out at the University of Genova, aimed at developing an integrated web-based GIS platform for the safe management and risk assessment of complex port areas exposed to intense wind actions. This activity, carried out through the Projects "Wind and Ports" and "Wind, Ports and Sea", financed by the European Territorial Cooperation Objective, Cross-border program "Italy–France Maritime 2007–2013", includes the realization of a wide in situ monitoring network, specific numerical codes for the multi-scale simulation of wind and wave fields, wind and wave forecasting algorithms, and statistical wind climate analyses. All the results obtained are made directly available to the port operators through a web-based GIS platform integrated into a global system for the safe and operational management of the port areas involved in the above projects. In particular, the monitoring and forecasting systems work out operative results in continuous mode. The generality of the implemented platform makes it immediately suitable for applications to any port reality worldwide and, even more, to any complex structural and infrastructural system under wind actions.